Implementasi Program "BerKreMo" dalam Meningkatkan Motivasi Belajar Anak-anak dari Keluarga Penerima Bantuan PKH di Kelurahan Nagahuta - Letare Winroriauli Sinaga, Hanna; Aulina Lubis, Mia (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2024)
The Family Hope Program (PKH) is a conditional cash transfer program that accelerates poverty alleviation in Indonesia by providing access to healthcare, education, and other basic social services. This study focuses on educational interventions for children receiving PKH in Nagahuta Village through Field Work Practice (PKL). The research employs a qualitative method with a descriptive approach to produce descriptive data from natural conditions. The practitioners conducted the "BerKreMo" (Learning through Playing, Creativity, and Motivation) mini project to address children's learning issues. The intervention results showed that the "BerKreMo" program successfully increased the learning motivation of children who were previously reluctant to study, making them more active and motivated. Activities that combined learning with play and creative endeavors effectively enhanced the children's interest and abilities in reading and learning English. This program also provided new insights to the community on the importance of interactive and creative education, raising awareness and community participation in supporting children's development. This study concludes that "BerKreMo" can improve children's behavior and comprehensively develop their social, cognitive, and emotional skills, creating a positive impact in the Nagahuta Village environment. Keywords: BerKreMo, Group Work, Nagahuta Village, Child Development, Family Hope Program.